Long-Term Observation and Treatment of Epithelioid Haemangioendothelioma of the Mediastinum: A Case Report - Zhi, Qiuli; Ma, Zhoupeng; Lin, Guansheng; Pan, Jiangfeng; Chen, Bingye (Frontiers in Surgery, 2021)
Epithelioid hemangioendothelioma(EHE) is a rare angiogenic tumour originating from vascular endothelial or pre-endothelial cells, and it can occur anywhere in the body, such as the liver, lung, bone, spleen, lymph nodes, parotid gland and thyroid. In the 5th revision of the World Health Organization classification, EHE was described as a malignant vascular neoplasm composed of epithelioid endothelial cells, distinct from epithelioid angiosarcoma. We herein report one patient with EHE of the left upper mediastinum who underwent resection and radiotherapy during the first therapeutic process. Multiple metastases occurred in the thoracic vertebrae 6 years later, and resection and multiple radiotherapies were performed. The patient's condition remained stable at the last review in October 2020, and it has been more than 8 years since her first admission. The reasonable “take-away” lessons from the case are active treatment and prolonged surveillance.